algebra

posted by .

using foil method
x^2 + (x+1)+(x+3)^2 =38 then combine

  • algebra -

    (x+3)^2 = x^2 + 6x + 9
    Now substitute that into your equation and combine terms.

    You not require parentheses around x+1 since you are not raising it to a power

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algebra (new one since I put "match" (bad speller)

    I have a few match problems that I can't figure out. 1.solve: 3x+5=x√7 (that's a radical sign) 2.factor: (2k+3)2-(2x+3)(y-2)-20(y-2)2 (the "2" after (2k+3) ans (y-2) is suppose to be a square sign. thanks if you can help, or …
  2. Algebra

    Use the foil method to find the product. (4x^6-7)(x^8-4) this is the answer that I got:4x^14-7x^8-16x^6+28
  3. Algebra

    How do you solve this factoring problem by foil method: 25x2=16
  4. college algebra

    would this be foil method? If so how do I solve. x-1 x-5 = x+3 x+4
  5. Math algebra

    how do you do this by using the FOIL method?
  6. Algebra

    Use the FOIL method to find the product (3x^2-5)(x^5-9)
  7. Intermediate Algebra

    Using the foil method,multiply....(2/5t-1)(3/5+1)
  8. Algebra

    I also need you to check and make sure that I am using the FOIL method correctly for this problem. #82). 9w-w^3 9w-w^3=w*(w^2-9) I have to factor out the GCF, which is “w”. 9-w^2=3^2-w^2= (3-w) (3+w) = (3-w) (w+3) 3-w=-(w-3) (3-w)(W+3)=-(w-3) …
  9. Algebra

    I also need you to check and make sure that I am using the FOIL method correctly for this problem. #82). 9w-w^3 9w-w^3=w*(w^2-9) I have to factor out the GCF, which is “w”. 9-w^2=3^2-w^2= (3-w) (3+w) = (3-w) (w+3) 3-w=-(w-3) (3-w)(W+3)=-(w-3) …
  10. algebra

    use the foil method (7-6y)(7-4y) thanks to who ever can help me

More Similar Questions